Integrasi Indoor dan Outdoor Learning pada Praktik Pengalaman Lapangan Program Studi Pendidikan Agama Islam - Arsyillah, Berlian Tahta; Mukarromah, Mukarromah; Fauzah, Nurul (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
Apart from being an activity that aims to provide real professional experience, Field Experience Practice (PPL) can also expand students' horizons in the formation of pedagogic, professional, personal and social competencies as prospective educators. To optimize the process and output_nya, the PAI study program of Darullughah Wadda'wah Bangil International Islamic University implements PPL through the integration of indoor and outdoor learning. PPL PAI through the integration of indoor and outdoor learning aims to provide reinforcement related to the practice of PAI study program field experience. Students not only gain experience in one institution (indoor learning), but also gain other experiences from various institutions (outdoor learning). This qualitative research aims to analyze these activities with a descriptive approach. The results of the study show that PPL PAI study program indoor learning is carried out at MTs and MA Dalwa Bangil under the auspices of Islamic boarding schools, while PPL PAI outdoor learning is carried out in several educational institutions outside the Darullughah Wadda'wah Bangil Islamic boarding school, precisely at the Alkhairiyah Foundation Surabaya Kindergarten, Alkhairiyah Elementary & Junior High School, MI Al Akbar Mosque, Al-Ghilmani Elementary School Surabaya, MTs Alif Lam Mim Surabaya and Al-Khadijah Junior High School Surabaya. Furthermore, the implementation of PPL for the PAI study program goes through the following stages: 1) debriefing, including: planning, 2) implementation and evaluation. The author argues that PPL PAI through the integration of indoor and outdoor learning can provide reinforcement related to the practice of field experience in the PAI study program. Students not only gain experience at one institution, but can also enrich experience from various partner institutions